2007
DOI: 10.1111/j.1365-313x.2007.03277.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4,5‐bisphosphate is important for stomatal opening

Abstract: SummaryPreviously, we demonstrated that a protein that binds phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P 2 ] inhibits both light-induced stomatal opening and ABA-induced stomatal closing. The latter effect is due to a reduction in free PtdIns(4,5)P 2 , decreasing production of inositol 1,4,5-trisphosphate and phosphatidic acid by phospholipases C and D. However, it is less clear how PtdIns(4,5)P 2 modulates stomatal opening. We found that in response to white light irradiation, the PtdIns(4,5)P 2 -bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 78 publications
6
81
0
1
Order By: Relevance
“…In addition, exogenous PtdIns(4,5)P 2 stimulates the internalization process in WT cells ( Figure 5B), which strongly suggests that vesicle trafficking, especially endocytosis, is affected by PIP5K2 through its product PtdIns(4,5)P 2 . These results are similar to previous findings that disruption of PIP5K4 inhibits proper endocytosis and membrane recycling in pollen tubes [21] and consistent with the report that PIP5K6 and PtdIns(4,5)P 2 positively regulate clathrin-dependent endocytosis [18].…”
Section: Pip5k2/ptdins(45)p 2 Regulates Vesicle Trafficking and Is Csupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, exogenous PtdIns(4,5)P 2 stimulates the internalization process in WT cells ( Figure 5B), which strongly suggests that vesicle trafficking, especially endocytosis, is affected by PIP5K2 through its product PtdIns(4,5)P 2 . These results are similar to previous findings that disruption of PIP5K4 inhibits proper endocytosis and membrane recycling in pollen tubes [21] and consistent with the report that PIP5K6 and PtdIns(4,5)P 2 positively regulate clathrin-dependent endocytosis [18].…”
Section: Pip5k2/ptdins(45)p 2 Regulates Vesicle Trafficking and Is Csupporting
confidence: 82%
“…The catalytic activities of using PtdIns4P as the preferred substrate to generate PtdIns(4,5)P 2 have all been characterized [15][16][17][18]. Studies have revealed the physiological functions of some PIP5Ks, including PIP5K1 in abscisic acid signaling [19]; PIP5K3 in root hair formation and growth [16,20]; PIP5K4 in stomata opening [21]; and PIP5K4-6 in pollen tube growth [17,22]. In addition, PIP5K9 regulates root growth and is involved in sugar signaling [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant PIP5K3 Protein Shows PtdIns4P 5-Kinase Activity in Vitro PIP5K3 was expected to have PtdIns4P 5-kinase activity because of its amino acid sequence similarity to PIP5K1 and PIP5K4, for which enzyme activity has been determined in vitro (Mikami et al, 1998;Elge et al, 2001;Westergren et al, 2001;Perera et al, 2005;Lee et al, 2007). To investigate the activity of PIP5K3, a fusion protein with glutathione S-transferase (GST) was expressed in E. coli cells.…”
Section: Resultsmentioning
confidence: 99%
“…These are classified into two subfamilies: proteins of subfamily A (PIP5K10 and PIP5K11) consist of dimerization and catalytic domains similar to those in the animal enzymes, while subfamily B proteins (PIP5K1 to PIP5K9) have an additional domain containing a repeat of the membrane occupation and recognition nexus motif (MORN motif) (Takeshima et al, 2000) at the N terminus. Currently, the biological functions of only PIP5K1, PIP5K4, and PIP5K9 have been elucidated as being involved in abscisic acid signaling, stomata opening, and sugar signaling, respectively (Mikami et al, 1998;Lee et al, 2007;Lou et al, 2007). A genomewide analysis has defined 606 Arabidopsis genes as the root hair morphogenesis transcriptome (Jones et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We recently identified a mechanism by which PtdIns(4,5)P 2 enhances stomatal opening. 6 Phosphatidylinositol 3-phosphate (PtdIns(3)P) functions as a positive effector of stomatal closing by activating ROS formation 5 and Ca 2+ oscillations. 4 Phosphatidylinositol 4-phosphate (PtdIns(4)P) similarly enhances stomatal closing.…”
Section: Introductionmentioning
confidence: 99%